(untitled) (International Journal of Environmental Sciences, 2025)
Over the past decade, the manufacturing industries have struggled a lot to gain the required performance. However, there exist only a few methodologies which can work to cut down the wastes by maintaining the product quality and simultaneously taking care of the sustainability aspect. Among these, Sustainable Lean Six Sigma (SLSS) has emerged as the prime choice for industry practitioners. Similarly, adopting SLSS in manufacturing organisations of emerging economies is pretty complex when compared to the developing economies. This major lack is due to the unavailability of a streamlined framework and a key set of enablers that could help in penetrating SLSS across the manufacturing organisation smoothly. Additionally, the unavailability of key factors that could map the performance of SLSS across the manufacturing organisations has been a key concern for the researchers and practitioners. The present study identifies 31 key enablers through the existing literature studies and experts that strongly influence the adoption of SLSS in manufacturing organisations. Furthermore, a set of 22 performance measures is also identified, which can help in measuring the adoption rate of SLSS in the manufacturing organisations. The identified enablers are further categorised into 5 broad categories, which include strategic and policy-oriented enablers, managerial and human capital enablers, process optimisation enablers, technology integration enablers, and organisational capability enablers. The present study utilises a decision support framework that includes a hybrid combination of the Robust Best Worst Method (RBWM) and the CoCoSo method. Under this hybrid approach, the prioritisation of shortlisted SLSS enablers is done through the RBWM method, whereas the ranking and prioritisation of the performance measures is done through the CoCoSo method. The results reveal that the strategic and managerial enablers possess a strong influence on the adoption of SLSS in the manufacturing organisations. Furthermore, it has been recommended that strong involvement of Management and appropriate consideration of sustainability factors for building the policy frameworks play an essential role in proper penetration of SLSS into the manufacturing organisation. The hybrid framework utilised in this study provides practical recommendations for practitioners working in the industries, as well as it acts as a foundation for academicians working in the direction of theoretical development for sustainable lean six sigma. The present study is one of the unique attempts that utilises a hybrid approach that not only identifies the key set of SLSS enablers but also identifies and prioritises the critical performance measures that influence its adoption.